2016
DOI: 10.4212/cjhp.v69i3.1555
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Dabigatran and Rivaroxaban Prescribing for Hospital Inpatients

Abstract: Background: Recent approval of the new oral anticoagulants dabigatran and rivaroxaban has led to rapid changes in anticoagulant prescribing practices. Postmarketing reports have highlighted safety concerns with these agents, and their use outside of evidence-based recommendations was noted at the authors' centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Direct comparisons of the data obtained from the present study and those obtained from previous studies would be difficult, since all studies employed different criteria for inappropriate prescriptions. Nevertheless, the four studies [12–14, 18] that adopted criteria similar to those in the present study reported frequencies of potentially inappropriate dabigatran prescriptions (from 2.0 to 31.2%) comparable to that observed for inpatients in the present study (11%). In contrast, three other studies [15–17] reported substantially higher values (from 34.1 to 51.1%) than the present study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Direct comparisons of the data obtained from the present study and those obtained from previous studies would be difficult, since all studies employed different criteria for inappropriate prescriptions. Nevertheless, the four studies [12–14, 18] that adopted criteria similar to those in the present study reported frequencies of potentially inappropriate dabigatran prescriptions (from 2.0 to 31.2%) comparable to that observed for inpatients in the present study (11%). In contrast, three other studies [15–17] reported substantially higher values (from 34.1 to 51.1%) than the present study.…”
Section: Discussionsupporting
confidence: 81%
“…To our knowledge, seven previous studies [12–18] reported the frequency of potentially inappropriate dabigatran prescriptions in real-world practice in different countries (Table 4). Direct comparisons of the data obtained from the present study and those obtained from previous studies would be difficult, since all studies employed different criteria for inappropriate prescriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, data from the GLORIA‐AF registry showed that AF guideline adherence requires improvement, as nearly half of low‐risk patients are overtreated, and that patients at high risk of stroke were undertreated with oral anticoagulants . Studies from Larock et al McDonald et al and Chowdry et al also reported high values of potentially inappropriate dabigatran prescriptions (31.2–51.1%), which corroborates the problem of off‐label doses with dabigatran.…”
Section: Resultsmentioning
confidence: 86%
“…Indeed published surveys report up to a third of hospital patients may receive an incorrect dose or are inappropriately prescribed a NOAC even when contraindicated. [11][12][13][14] The International Society on Thrombosis and Haemostasis (ISTH) 15 and European Heart Rhythm Association (EHRA) 16 provide practical guidance on the use of NOACs, emphasizing the need for appropriate patient selection, minimizing unnecessary drug-drug interactions, and monitoring for dosing errors, adherence, or adverse effects. Several models of care for the optimal follow-up and clinical monitoring of patients receiving therapy with NOACs have been proposed, 17 but there are currently no published studies evaluating the effectiveness of a nurse-led approach.…”
mentioning
confidence: 99%